Online Warehouse Application at PT. PLN (Persero) ULP Lhokseumawe City - Yusma Subhina; Salahuddin Salahuddin; Muhammad Khadafi (Politeknik Negeri Lhokseumawe, 2025)
PT PLN (Persero) ULP Lhokseumawe City is one of the State-Owned Enterprises engaged in the provision of electricity for distribution to the community. PT PLN (Persero) ULP Lhokseumawe City has a warehouse that serves as a material storage facility, functioning as a transaction location for incoming and outgoing materials, as well as for monitoring material stocks. The warehouse serves as a storage facility for materials required by all companies. Materials are tools used to meet the needs of workers and the community in supporting the distribution of electricity. Without materials, activities related to electricity cannot be carried out; therefore, it is necessary to have information about material stocks to ensure the smooth operation of a job. At the PLN ULP Lhokseumawe City office, material data collection is still conducted manually using notes or transaction recording books. If you pay attention, the manual system is not safe, because if the data is lost it cannot be recovered. Additionally, materials can be shipped from the warehouse without the supervisor's knowledge, resulting in material stock reports that do not accurately reflect the material stock in the warehouse. Material inventory is a common issue that arises when material stocks run low and technical officers require materials to support the distribution of electricity to customers. In the warehouse, some materials are rarely issued by warehouse officers, resulting in a significant accumulation of unused materials. Therefore, an application is needed to control materials in the PT PLN ULP Lhokseumawe City warehouse based on the web. The purpose of creating this application is to enable the monitoring, management, and control of materials in the warehouse, allowing for the printing of reports based on the materials stored. This can facilitate the supervision of the release of goods that are not carelessly issued and technical officers are not short of material stock. These reports will later be compiled by the TUG (Warehouse Administration) as determined by PT.PLN (Persero).